Kebijakan Hukum Pidana Sanksi Kebiri Kimia dalam Perspektif HAM dan Hukum Pidana Indonesia - Nur Hafizal Hasanah; Eko Soponyono (University of Udayana, 2018)
The sexual offense against children is a serious crime and an act of violation against human rights. One of the government is an attempt to anticipate the increase of sexual offense against children is to release Perpu No 1 of 2016 second amendment of UU No 23 of 2002 about child protection. Perpu No. 1 is then passed into UU No. 17 of 2016 about stipulation of Perpu No. 1 of 2016. The regulation of the Perpu is about the denunciation of the perpetrator of a sexual offense, an especially sexual offense against children. The perpu also regulates the existence of criminal sanction and action sanction. The action referred to in the Perpu in the form of chemical castration and accompanied by rehabilitation. Research method uses normative research method by using the Statue approach and the analytical and conceptual approach. the implementation of chemistry castration is considered a violation of human rights. Penalties through castration can be qualified as a cruel and inhuman punishment and not in accordance with Indonesia's constitution and commitment in the field of human rights. The provision of article 28G paragraph (2) of the Indonesian constitution states that